Impact of Security Concerns on Girls’ Educational Access: A Study of Parental Perceptions and Societal Challenges in Kanpur City - Rahul Srivastava; Prakash Chandra Jha; Priyanka Kumari; Sidhant Kumar; Abhishek Vardhan; Kumari Menka (Journal of Pharmacy and Bioallied Sciences, 2025)
Background: Girls’ education is crucial for societal progress, yet security concerns remain a significant barrier in various regions. In Kanpur City, India, many families cite safety issues as a reason for limiting educational access for girls. This study aims to examine the impact of security concerns on girls’ education, focusing on parental perceptions and societal influences affecting educational equality. Materials and Methods: A cross-sectional survey was conducted with 2000 participants, including parents, students, school administrators, and community leaders in Kanpur City. The survey gathered data on demographic characteristics, perceived security risks, and the impact of these concerns on educational decisions. Responses were analyzed to identify key factors that contribute to safety concerns and to determine how these perceptions influence girls’ school attendance and retention. Results: Results indicated that 70% of participants agreed that security concerns significantly affect decisions regarding girls’ education. The main concerns included harassment (60%), road safety (25%), and fears of kidnapping (10%). Additionally, 30% of parents reported discontinuing their daughters’ education due to these fears. Respondents highlighted the need for improved school infrastructure, public awareness campaigns, safe transportation options, stricter law enforcement, and government incentives to support girls’ education. Conclusion: The findings reveal a strong association between security concerns and limited educational opportunities for girls. Addressing these issues through enhanced safety measures, community education, and government support could improve educational equity and encourage families to invest in girls’ education. This study underscores the importance of addressing security to foster an inclusive educational environment in Kanpur City.